ONLINE GAMES AS TOOLS OF HYBRID WARFARE - Сохацький, Олександр Ю.; Шухманн, Вадим А. (Journal of Strategic Economic Research, 2023)
The article examines the use of online games as tools of hybrid warfare, which became possible as the result of the digitalization of global space. Considering the widespread prevalence of this type of entertainment among the population of most countries of the world, the consequences of such use is a new, complex problem, the solution of which requires a comprehensive study within the boundaries of the states that are victims of such aggression and the corresponding reaction of the international environment. In particular, it is definied that the return of the argument of force in international relations has had a negative impact on the online gaming industry. Recently, states pursuing geopolitical goals, primarily Russia, actively began to use virtual games as new means of influencing the country’s population – victims of aggression, together with information propaganda, cyber – attacks, fake news, etc. It has been proven that the use of online games in hybrid warfare can have serious consequences for countries and their national security. We can cite Ukraine as an example, where during a large-scale bloody war, Russia simultaneously uses all informational tools to destabilize the internal situation in the country, undermine the unity of the population, in particular, demoralize the youth by promoting force and cruelty through the achievement of victory in the game, the destruction of opponents, the cultivation of narratives of the state- aggressor, its ideology, etc. It was determined that online games are actively used to advertise political ideas and support the influential groups needed by the aggressor country, to collect intelligence information, which is also then used for cyber-attacks or other forms of hybrid warfare. The article proposes specific measures that should be applied in Ukraine in the security, economic, media and educational spheres regarding the dissemination of information about a group of specific online games, which, indeed, have all the characteristics of an information weapon.